Traffic deaths of reindeer in Finland during 1974 — 83 - Nieminen, Mauri; Leppäluoto, Juhani (Rangifer, 1985)
During 1974 — 83 a total of 23.298 reindeer died in traffic accidents in Finland. Vehicles killed 19.962 reindeer (85,7% of traffic deaths) and trains 3.336 reindeer (14,3%). During 1978 — 82 the majority of reindeer killed by vehicles were hinds (52,2%) and calves (24,6%). Reindeer road deaths were concentrated in the southern and central, heavily trafficked herding areas. Most reindeer were killed by vehicles in the marked herding areas of Pudasjårvi, Kuusamo, Raudanjoki and Sodankyiå. The most destructive section of road was highway number 20 between Pudasjårvi and Taivalkoski where 559 reindeer died during 1978 — 82 on a 36 km stretch. The worst railway stretch was between Ii and Kemi where an average of 115 reindeer/10 km died during 1976 — 82. Most reindeer died in traffic in November, December and January during the soft snow period when the movement of reindeer is most difficult. In summer, most reindeer died in traffic in July — August. The number of reindeer deaths on the roads in May — September depended slightly on the temperature in the different months (r=0,398). Throughout the whole reindeer herding area the amount of reindeer deaths also depended on the average 24-hour traffic (r=0,445).Porojen liikennekuolemat Suomessa 1974 — 83.Abstract in Finnish / Yhteenveto: Vuosina 1974—83 kuoli liikenteesså Suomessa yhteenså 23.298 poroa. Auton alle jåi 19.962 poroa (85,7% liikennekuolemista) ja junan alle 3.336 poroa (14,3%). Vuosina 1978—82 oli autojen alle jååneistå poroista suurin osa vaatimia (52,2%) ja vasoja (24,6%). Porojen maantiekuolemat keskittyivåt etelå- ja keskiosan pieniin ja runsaasti liikennoityihin paliskuntiin. Eniten poroja jåi auton alle Pudasjårven, Kuusamon, Raudanjoen ja Sodankylån merkkipiirien paliskunnissa. Tuhoisin tieosuus oli valtatie n:o 20 vålillå Pudasjårvi—Taivalkoski, jossa kuoli vuosina 1978—82 yhteenså 559 poroa 36 km:n matkalla. Pahin rataosuus olivålillå li—Kemi, jossa kuoli vuosina 1976—82 keskimaårin yli 115 poroa/10 km. Eniten poroja kuoli liikenteesså marras-, joulu- ja tammikuussa pehmeån lumen aikaan, jolloin porojen liikkuminen vaikeutui eniten. Kesållå kuoli liikentesså eniten poroja heinå—elokuussa. Touko—syyskuussa porokuolemien måårå maanteillå riippui eri kuukausina hieman ilman låmpotilasta (r=0,398). Koko poronhoitoalueella porokuolemien måårå riippui myos keskimååråisestå vuorokautisesta liikenteestå (r=0,445).Renarnas trafikdödlighet i Finland under åren 1974-1983Abstract in Swedish / Sammandrag: Under åren 1974—83 dog i trafiken i Finland sammanlagt 23.298 renar. Av dessa blev 19.692 påkorda (85,7%) av bilar och 3.336 av tåg (14,3%). Under åren 1978—82 var merparten av de av bilar påkorda renarna vajor (52,2%) och kalvar (24,6%). Renarnas landsvågsdodlighet koncentrerade sig till de små hårt trafikerade renbeteslagen i de mellersta och de sydliga delarna av renskotselområdet. Flest renar blev overkorda av bilar i Pudasjårvi, Kuusamo, Raudanjoki och Sodankyiå mårkesdistrikts renbeteslag. Den vårsta vågstråckan var riksvåg nr. 20 mellan Pudasjårvi och Taivalkoski, dår under åren 1978—82 sammanlagt 559 renar dog på en stråcka av 36 km. Den varsta jårnvågsstråckan var mellan li och Kemi, dår under åren 1976—82 i genomsnitt over 115 renar/10 km dog. Flest renar dog i trafiken i november, december och januari då snon var som mjukast och renarnas rorlighet forsvårades som mest. Under sommaren dog flest renar i juli—augusti. Under maj—september fanns det en korrelation mellan renarnas trafikdodlighet på landsvågarna och luftens temperatur (r=0,398). I hela renskotselområdet fanns det också en korrelation mellan rendodligheten och den genomsnittliga dygnstrafiken (r=0,445).